2020
DOI: 10.1038/s41467-019-13972-y
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose bNAb cocktail or abbreviated ART post-exposure regimens achieve tight SHIV control without adaptive immunity

Abstract: Vertical transmission accounts for most human immunodeficiency virus (HIV) infection in children, and treatments for newborns are needed to abrogate infection or limit disease progression. We showed previously that short-term broadly neutralizing antibody (bNAb) therapy given 24 h after oral exposure cleared simian-human immunodeficiency virus (SHIV) in a macaque model of perinatal infection. Here, we report that all infants given either a single dose of bNAbs at 30 h, or a 21-day triple-drug ART regimen at 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 56 publications
2
45
1
Order By: Relevance
“…We obtained this type of outcome with our previous adenovirus-based vaccine ( 12 ), where the cell-associated viral loads were significantly lower in SAd7+Protein vaccinated macaques compared to control animals. In related studies in primates, we showed that bNAbs can limit viral seeding when present within 24 to 30 h of exposure to Tier 2 SHIV SF162P3 ( 28 , 45 ) and that it is possible to reduce the levels of tissue viral DNA in macaques exposed to Tier 1 SHIV in the presence of a single human monoclonal antibody directed to V1V2 ( 46 ). In the current experiment, both regimens significantly lowered viral DNA copies in lymphoid and gut tissues tested.…”
Section: Discussionmentioning
confidence: 92%
“…We obtained this type of outcome with our previous adenovirus-based vaccine ( 12 ), where the cell-associated viral loads were significantly lower in SAd7+Protein vaccinated macaques compared to control animals. In related studies in primates, we showed that bNAbs can limit viral seeding when present within 24 to 30 h of exposure to Tier 2 SHIV SF162P3 ( 28 , 45 ) and that it is possible to reduce the levels of tissue viral DNA in macaques exposed to Tier 1 SHIV in the presence of a single human monoclonal antibody directed to V1V2 ( 46 ). In the current experiment, both regimens significantly lowered viral DNA copies in lymphoid and gut tissues tested.…”
Section: Discussionmentioning
confidence: 92%
“…Stimulating effectors using vaccines has been shown to suppress viral replication and lower the set-point viremia [ 47 , 48 ], but several additional design challenges must be overcome, including the need to stimulate effectors early enough and, interestingly, prevent effector exhaustion due to the vaccine [ 49 ], for the successful deployment of T cell vaccines [ 50 ]. Further, such strategies may not work in children, where bNAbs may elicit control without effector responses, possibly due to the inadequately developed immune system [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…As in the previous study, all animals that received the bNAb therapy were free of viremia in both the plasma and tissue measurements 6 months after treatment. A later study showed that in infant macaques, treatment with the same combination of bNAbs at 30 h post SHIV-SF162P3 challenge, but not at 48 h, was sufficient for keeping the animals from becoming infected (Shapiro et al, 2020). These studies show that bNAb therapy could be used for treating early infections if the treatment is started within a very early window of exposure.…”
Section: Learning From Passive Infusion Efficacy Studies Preclinical mentioning
confidence: 88%